2016
DOI: 10.5194/hess-20-1211-2016
|View full text |Cite
|
Sign up to set email alerts
|

Creating long-term gridded fields of reference evapotranspiration in Alpine terrain based on a recalibrated Hargreaves method

Abstract: Abstract.A new approach for the construction of highresolution gridded fields of reference evapotranspiration for the Austrian domain on a daily time step is presented. Gridded data of minimum and maximum temperatures are used to estimate reference evapotranspiration based on the formulation of Hargreaves. The calibration constant in the Hargreaves equation is recalibrated to the Penman-Monteith equation in a monthly and station-wise assessment. This ensures, on one hand, eliminated biases of the Hargreaves ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…For simplicity, the climatic variables were considered to be independent in the final step of the uncertainty estimation, which involved the propagation of the uncertainty of each climatic variable through the Penman-Monteith equation. Haylock et al (2008) pointed out that the variance of the kriging, which in this paper was used to estimate the uncertainty of each climatic grid, is not a true estimation of the uncertainty; however, an evaluation of the uncertainty estimations of each variable showed a good agreement between the MAE values and the estimated uncertainty values. Unfortunately, the uncertainty of ET o could not be verified because an independent subset of observatories that collected all variables was required to calculate ET o but was not available.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…For simplicity, the climatic variables were considered to be independent in the final step of the uncertainty estimation, which involved the propagation of the uncertainty of each climatic variable through the Penman-Monteith equation. Haylock et al (2008) pointed out that the variance of the kriging, which in this paper was used to estimate the uncertainty of each climatic grid, is not a true estimation of the uncertainty; however, an evaluation of the uncertainty estimations of each variable showed a good agreement between the MAE values and the estimated uncertainty values. Unfortunately, the uncertainty of ET o could not be verified because an independent subset of observatories that collected all variables was required to calculate ET o but was not available.…”
Section: Discussionmentioning
confidence: 79%
“…Climate grid generation involves many sources of data uncertainty, including uncertainty related to the observation, the interpolation process and other sources (Haylock et al, 2008). In this paper, we assumed that uncertainty was only related to the estimation processes, i.e., gap filling and interpolation.…”
Section: Uncertainty Estimation In the Climatic Gridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other regional studies have created gridded estimates of AED in Austria (Haslinger and Bartsch, 2016) and Australia (Donohue et al, 2010). Regional studies of trends in AED have seen varied results, with increasing AED seen in Romania (Paltineanu et al, 2012), Serbia (Gocic and Trajkovic, 2013), Spain (Vicente-Serrano et al, 2014), some regions of China (Li and Zhou, 2014) and Iran (Azizzadeh and Javan, 2015;Hosseinzadeh Talaee et al, 2013;Tabari et al, 2012), decreasing AED in Northeast India and regions in China (Yin et al, 2009;Song et al, 2010;Shan et al, 2016;Zhao et al, 2015;Zhang et al, 2015;Lu et al, 2016) and regional variability in Australia (Donohue et al, 2010) and China (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach consists in using spatial interpolation to estimate the value of missing variables at the desired locations using data from nearby stations, an option that Tomas-Burguera et al (2017) showed to perform better than FAO-PMT or other simplied models such as Hargreaves and Samani, at least in the Iberian Peninsula (IP). This methodology have been tested in other regions, such as Greece (Mardikis et al, 2005), China (McVicar et al, 2007), Austria (Haslinger and Bartsch, 2016), or Great Britain (Robinson et al, 2017).…”
mentioning
confidence: 99%